Optimizing the management of castration‐resistant prostate cancer patients: A practical guide for clinicians. Issue 14 (11th August 2020) - Shore, Neal D.; Drake, Charles G.; Lin, Daniel W.; Ryan, Charles J.; Stratton, Kelly L.; Dunshee, Curtis; Karsh, Lawrence I.; Kaul, Sanjeev; Kernen, Ken; Pieczonka, Christopher; Sieber, Paul; Stewart, Christopher; et al.
Abstract: Background: Advanced prostate cancer (PC) patients, especially those with metastatic prostate cancer (mPC), often require complex management pathways. Despite the publication of clinical practice guidelines by leading urological and oncological organizations that provide a substantial and comprehensive framework, there are numerous clinical scenarios that are not always addressed, especially as new treatments become available, new imaging modalities are developed, and advances in genetic testing continue. Methods: A 14‐member expert review panel comprised of urologists and medical oncologists were chosen to provide guidance on addressing specific topics and issues regarding metastatic castration‐resistant prostate cancer (mCRPC) patients. Panel members were chosen based upon their experience and expertise in the management of PC patients. Four academic members (two urologists and two medical oncologists) of the panel served as group leaders; the remaining eight panel members were from Large Urology Group Practice Association (LUGPA) practices with proven experience in leading their advanced PC clinics. The panel members were assigned to four separate working groups, each assigned a specific mCRPC topic to review and discuss with the entire panel. Results: This article describes the practical recommendations of an expert panel on the management of mCRPC patients. The target reading audience for this publication is all providers (urologists, medical oncologists, radiation oncologists, or advanced practice providers) who evaluate and manage advanced PC patients, regardless of their practice setting. Conclusion: The panel has provided recommendations for managing mCRPC with regard to specific issues: (a) biomarker monitoring and the role of genetic and molecular testing; (b) rationale, current strategies, and optimal sequencing of the various approved therapies, including hormonal therapy, cytotoxic chemotherapy, radiopharmaceuticals and immunotherapy; (c) adverse event management and monitoring; and (d) imaging advanced PC patients. These recommendations seek to complement national guidelines, not replace them, and a discussion of where the panel agreed or disagreed with national guidelines is included.